THE EFFECTIVENESS OF TOTAL PHYSICAL RESPONSE TO IMPROVE STUDENTSâ€™ VOCABULARY MASTERY - Bigar Rahasia Siswa; Rini Fitria; Cut Dara Ilfa Rahila (INOVISH JOURNAL, 2020)
The research is aimed to know whether there is a significant difference of studentâ€™s vocabulary mastery between those who are taught by using Total Physical Response and those who are taught by using Direct Method. The researcher took the ninth grade student of MambaÃºl Hikmah Islamic Boarding School Magelang as the population. There were 80 student. We used total random sampling and divided the student into two groups, group A as the Experimental group was taught using â€œTotal Physical Responseâ€and group B as the control group was taught by using â€œDirect Methodâ€. The methods used to collect the data are documentation pre-test and post-test answer sheet. There were two tests given in this research. They were pre-test and post-test. To analyze the data the researcher used comparative analysis. The comparative formula of the data analysis used t-test calculation. The researcher used t-test to analyze the data. In which the pre-test score group A is 53, 275 that was higher than the second group. The post test score of group A is 67, 25 that was higher than the group B as the Control group. While t-test proves that difference is significant because the result of T-test is higher that the figure shown on the t-table. Based on the above result, the researcher concludes that there is significant difference between the student who are taught using â€œTotal Physical Responseâ€ and those who were taught using â€œDirect Methodâ€. It is better for English teacher to use â€œTotal Physical Responseâ€ as one of technique in teaching vocabulary mastery for junior high school especially in the Islamic Boarding School.